Caste-based reservations and human development in India - Chalam, K. S. (Kurmana Simha), 1948- (Sage Publications, 2007)
Caste-based reservations have existed in India for more than a century. Initially. introduced by the British to bring about equal of opportunity in education, reservation. was later extended to other sectors of the development process to overcome the. economic inequalities attributed to caste. Even today, concepts like affirmative. action and quotas are being debated to justify reservation. Caste-based Reservations and Human Development in India comprehensively. analyses the impact of such reservations on the target groups, as well as on. major human development indices, taking into considerat.